The History of the Transjugular Intrahepatic Portosystemic Shunt - Ferral, Hector; Lopez-Benitez, Ruben (Seminars in Interventional Radiology, 2023)
Few, if any, developments in the past three decades have advanced the field of portal hypertension more than the use of transjugular intrahepatic portosystemic shunts (TIPS). Initially pursued in animal studies more than 50 years ago, and discovered serendipitously, TIPS quickly became used clinically in the treatment of refractory esophageal hemorrhage. The technique is now used for many other clinical indications as well as to bridge patients to liver transplantation. Several technical advancements have improved short- and long-term outcomes of the procedure. This article will review the development of TIPS from its inception to the current state of care regarding this important minimally invasive option for patients with portal hypertension.
Keywords: interventional radiology; transjugular intrahepatic portosystemic shunt; history